STRENGTHENING THE ORGANIZATIONAL CULTURE OF MSMES ON THE KARIMUN COAST TO IMPROVE BUSINESS PERFORMANCE AND SUSTAINABILITY - Ramli; Bambang Satriawan; Raja Rafiza; Dwi Kartika Sari (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
MSMEs in the area coast play significant role​ in jack up economy local , but Still face a number of problem in management business , especially related with weakness culture organization . Activities devotion to public This aim For strengthen tradition organizations in coastal MSMEs Beach Karimun use repair performance And sustainability business . The method used is a participatory approach through outreach, training, and mentoring for 35 MSMEs. Data collection was conducted through observation, interviews, and questionnaires before and after the intervention. The results of these activities showed an improvement in organizational culture elements, such as work commitment, internal communication, operational discipline, and business innovation. This improvement impacted business performance, as seen through increased turnover, an increase in the number of customers, and product development. In addition, MSMEs also demonstrated a better ability to adapt to changes in the business world, thus supporting business continuity. Thus, strengthening organizational culture through community service programs has proven to be an effective strategy in improving the performance and sustainability of MSMEs in coastal areas .